(untitled) (Research, Society and Development, 2020)
This paper is aimed at further researching two problems which question the role of PPAT (Pejabat Pembuat Akta Tanah) to implement credit binding in the bank. PPAT is an official certifier of title deeds which is made and used as evidence that certain legal actions have been carried out regarding land rights or ownership rights in Indonesia. This paper will also discuss the implementation of making mortgage rights on bank loans. The method used was through analytical descriptive methods with normative juridical approach. Data were collected through literature research that were analyzed qualitatively through juridical interpretation based on relations between legal principles approach based on the legal material by examining the theories, concepts, principles of law and legislation. It is found that the authority of the PPAT on granting land mortgage rights on bank loans is where the PPAT handles the implementation of credit agreements in the Bank until the granting of mortgage rights can be placed on the said land. The implementation of making mortgage rights on bank loans was followed by a promise to provide mortgage rights. The granting of Mortgage Rights is also preceded by an assurance to arrange for Mortgage Rights as a guarantee of paying off certain debts, which are set forth in the debt agreement concerned or other agreements that cause the debt.